Interferon α sensitisation induced fatal renal insufficiency in a patient with chronic myeloid leukaemia: case report and review of literature. Issue 8 (27th July 2006) - Colovic, M; Jurisic, V; Jankovic, G; Jovanovic, D; Nikolic, L J; Dimitrijevic, J
Abstract : Renal dysfunction as a sequel to extended interferon alfa (IFNα) treatment in chronic myeloid leukaemia (CML) has been reported previously in six patients. An additional patient is presented with Philadelphia chromosome positive (Ph+) CML and nephrotic syndrome in whom initial renal insufficiency developed after only one month of low dose IFNα therapy. The renal biopsy showed a focal segmental mononuclear cell infiltration, basal membrane thickening, and deposits of immunoglobulins (IgG; IgAGM IC3). In spite of discontinuation of IFNα, renal function deteriorated and the patient died six months later. This case represents an instance of fatal kidney insufficiency as an untoward effect of sensitisation to the IFNα, confirmed by modified Coombs assay.